Students’ Perception of Intercultural Communication Competence in Developing Speaking Skills - Rokhayati, Titi (UICELE, 2026)
This study investigates the students’ perception of intercultural communication competence in developing speaking skills through a qualitative research approach. The research aims to explore how students’ understanding of cultural diversity, communication norms, and intercultural awareness contribute to the improvement of their speaking performance in English. The participants of this study were second semester of university students enrolled in English learning classes that integrated intercultural communication activities into classroom practice. Data were collected through classroom observations, semi-structured interviews, reflective journals, and speaking performance documentation. The findings reveal that intercultural communication competence contributes to the development of students’ speaking skills, particularly in terms of fluency, accuracy and appropriateness. Students became more aware of cultural differences in communication styles, politeness strategies, and contextual language use, which helped them communicate more effectively and confidently in English. In addition, intercultural learning activities encouraged active participation, critical reflection, and greater motivation to practice speaking. The study concludes that integrating intercultural communication competence into English language learning can create meaningful communicative experiences and enhance students’ speaking abilities in both linguistic and sociocultural aspects. Therefore, intercultural-oriented instruction is recommended to support more contextual and communicative English learning practices in higher education.